Inclusive red meat value chains for women and young farmers in East and Southern Africa - International Livestock Research Institute (International Livestock Research Institute, 2022)
This film was made for the launch of the 'Inclusive Red Meat Value Chains for Women and Young Farmers in East and Southern Africa (K’Lusa) Project' in Tsholotsho, Zimbabwe. Implemented in Malawi and Zimbabwe, the K'Lusa aims to increase participation of smallholder farmers in market-oriented climate-smart value chains.. K'Lusa is a six-year project with a USD 67.8 million funding from IFAD. It is implemented by Solidaridad, ILRI and the Global Roundtable for Sustainable Beef.